2013
DOI: 10.1371/journal.pntd.0002383
|View full text |Cite
|
Sign up to set email alerts
|

The Functional, Social and Economic Impact of Acute Encephalitis Syndrome in Nepal – a Longitudinal Follow-Up Study

Abstract: BackgroundOver 133,000 children present to hospitals with Acute Encephalitis Syndrome (AES) annually in Asia. Japanese encephalitis (JE) accounts for approximately one-quarter of cases; in most cases no pathogen is identified and management is supportive. Although JE is known to result in neurological impairment, few studies have examined the wider impact of JE and AES on patients and their families.Methodology/Principal FindingsChildren (aged 1 month–14 years) with AES were assessed 5–12 months after discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 28 publications
1
38
1
Order By: Relevance
“…JEV is responsible for numerous cases of encephalitis worldwide, is associated with a high mortality rate (up to 30%), and the majority of surviving children suffer from functional impairment, especially in behavior, language, and limb use. 77,78 In one series of over 100 children in Malaysia, those with poor outcome at hospital discharge were more likely to have experienced seizures before or at hospital admission, to have a faster heart rate, to have required intubation, to have a reduced Glasgow coma score, and to have abnormal motor signs. 79 Despite the prevalence and severity of JE, however, neuroimaging biomarkers have not been well characterized.…”
Section: Neuroimaging Biomarkers and Outcomesmentioning
confidence: 99%
“…JEV is responsible for numerous cases of encephalitis worldwide, is associated with a high mortality rate (up to 30%), and the majority of surviving children suffer from functional impairment, especially in behavior, language, and limb use. 77,78 In one series of over 100 children in Malaysia, those with poor outcome at hospital discharge were more likely to have experienced seizures before or at hospital admission, to have a faster heart rate, to have required intubation, to have a reduced Glasgow coma score, and to have abnormal motor signs. 79 Despite the prevalence and severity of JE, however, neuroimaging biomarkers have not been well characterized.…”
Section: Neuroimaging Biomarkers and Outcomesmentioning
confidence: 99%
“…Michael J et al showed similar findings in there study that there was significant association between mortality and low income group (P < 0.01). 13 29(66%) patients had Glasgow Coma Score < 8 on admission reflecting impaired consciousness at the time of presentation, which had significant association(P=0.02) with outcome, 9(53%) patients of follow up completed group had Glasgow Coma Score < 8 on admission and all the 11(100%) patients (Ta b le-1) who died had Glasgow Coma Scale < 8 on admission. In this study there was no association between duration of fever with outcome.…”
Section: Discussionmentioning
confidence: 95%
“…Two of the cases had JE, but none of the ones with non-JE AES died after discharge from hospital. The only other studies that compared outcomes in JE and non-JE AES were the ones by Griffiths et al, (2013) (20) and Rayamajhi et al, (2007) (21). Both of the studies were from Nepal.…”
Section: Discussionmentioning
confidence: 99%